Effective and safe: Long-term aerosol disinfection of slightly acidic electrolyzed water causes no harm in rats - Takanori Oikawa; Kana Akinaga; Megumi Yanagida; Wataru Yamazaki; Tomoko Sato; Yuki Mukoda; Koya Terada; Yuriko Fujii; Misako Higashiya; Shinji Yamasaki; Takahiro Adachi; Shinsuke Seki (PLoS ONE, 2026)
Slightly acidic electrolyzed water (SAEW) has been shown to possess strong bactericidal and virucidal properties, making it a promising candidate for spatial disinfection. In this study, we rigorously evaluated the efficacy and safety of SAEW for aerosol disinfection under controlled conditions. Laser particle size distribution analysis confirmed uniform aerosolization. Additionally, analysis of chlorine concentration ensured stable disinfection conditions. Moreover, SAEW exhibited potent sterilization effects against the model organism Escherichia coli in both direct-contact and aerosol-disinfection experiments. Notably, long-term exposure assessments in rats revealed no adverse effects on body weight, food and water intake, and organ function and histology. Conclusively, these results indicate that SAEW is a highly effective and safe disinfectant for controlling airborne and droplet-mediated infections. In addition to preventing the spread of infectious diseases, including coronaviruses, SAEW is expected to be effectively utilized in the veterinary, agricultural, and food industries.